Prevalence and contamination patterns of Listeria monocytogenes in Pleurotus eryngii (king oyster mushroom) production plants - Xu, Jiang; Wu, Shi; Liu, Ming; Xiao, Zitian; Peng, Yangyang; He, Huanqing (Frontiers in Microbiology, 2023)
Listeria monocytogenes is a major foodborne pathogen that is well known as high mortality rate upon infected. Recent years, edible mushroom has also been found to be an important source of L. monocytogenes, but the contamination sources in Pleurotus eryngii (king oyster mushroom) was unclear. In this study, a total of 203 edible mushrooms and environment samples from four P. eryngii production plants were obtained. As a result, 29 samples (14.3%) were positive for L. monocytogenes, including 8 mushroom samples (13.3%, 8/60) and 21 associated environment samples (14.7%, 21/143). The contamination of L. monocytogenes in plant A and B were more severe that is likely to originate from mycelium stimulation machine. The isolates belonged to serogroup II.1 (4b-4d-4e), I.1 (1/2a-3a) and I.2 (1/2c-3c) and MLST revealed that these strains belonged to 5 different sequence types (ST3, ST121, ST9, ST87 and ST224). The ST121 and ST3 isolates were only found in plant A and plant B, respectively. The isolates were carried hly (29/29, 100%), inlB (23/29, 79.3%), inlA (29/29, 100%), inlC (29/29, 100%), inlJ (29/29, 100%), actA (19/29, 65.5%), iap (29/29, 100%), plcA (26/29, 100%), plcB (29/29, 100%), prfA (27/29, 93.1%) and mpl (29/29, 100%). Further study of inlA sequencing showing 65.5% of strains (19/29) contained full-length InlA that required for host cell invasion, whereas the mutation lead to PMSC at position 492 (type 6) on inlA alleles. All isolates in this survey were sensitive to gentamicin, kanamycin, sulbactam/ampicillin, trimethoprim-sulfamethoxazole, tetracycline and doxycycline, the highest resistance is rifampicin (37.9%), followed by penicillin (24.1%) and ciprofloxacin (10.3%). Most of multiply resistant strains isolated from raw material and equipment of the P. eryngii processing lines. Our study reflects the contamination patterns and potential risk of L. monocytogenes infection in P. eryngii production plants. The persistence of specific isolates (such as ST121 and ST3) may be assist with contamination. In accordance with these results, the control of L. monocytogenes should focus on the environment materials especially in mycelium stimulation stage. However, effective Listeria monitoring programs will allow for improved development of Listeria control measures in order to minimize cross-contamination in processing of P. eryngii.